Vilnius Market Подгале: Origin and Existence of the Name - Sinočkina, Birutė (Slavistica Vilnensis, 2024)
The article is devoted to the Russian name of the oldest Vilnius covered market (lit. Halės turgus), the history of which is directly related to the ups and downs of the political life of Lithuania, important historical events, engineering and technical achievements in the field of civil engineering at the turn of the 19th–20th centuries. The change in the urban landscape and the emergence of a new accent in it, the change of authorities and the dominant language in the country, specific of the motley social and speech environment in the city as a whole and on its trading floors affected the difficult history of the new name. The immediate subject of analysis was the word Подгале (Podhale), which goes back to the Polish nominative phrase Pod Halą with the reference word hala (← German Halle). Since an important object of urban infrastructure is necessarily displayed on city plans and recorded in signs to them, the article examines in detail these documentary sources from different historical periods and in different languages: Russian — from the time of the Tsarist Empire; Polish — pre-war and inter-war; Lithuanian — after the First World War. Along with the plans of the corresponding time, other sources of information are analyzed — address books and postcards with images of the object of interest to us, which to a lesser extent can claim to be historical evidence, but often reflect the actual existence of naming among townspeople. The article traces the role of the state Lithuanian language in the fate of the unofficial Russian urbanonym.